2013
DOI: 10.1108/02640471311299119
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility assessment of creating an inter‐library loan system and document delivery services in public libraries of Fars Province (Iran)

Abstract: PurposeThe aim of this research is to display an applied and descriptive survey, assessing the feasibility of creating an inter‐library loan (ILL) system and document delivery services in public libraries of Fars Province (Iran).Design/methodology/approachThe tool for gathering data in this study is a questionnaire distributed to 254 people from public library managers and librarians in Fars Province. Data analysis was performed with statistical software SPSS (version 16), using descriptive statistics and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…The studies on children and adolescents' interest in reading printed books showed that teens found it boring to read printed books and believed using them belonged to the past [32]. Nowadays, considering scientific and technological advances, replacing old with modern media such as ebooks and audiobooks can help raise people's awareness [33].…”
Section: Discussionmentioning
confidence: 99%
“…The studies on children and adolescents' interest in reading printed books showed that teens found it boring to read printed books and believed using them belonged to the past [32]. Nowadays, considering scientific and technological advances, replacing old with modern media such as ebooks and audiobooks can help raise people's awareness [33].…”
Section: Discussionmentioning
confidence: 99%
“…Perpustakaan yang modern dituntut untuk lebih kreatif dan inovatif dalam mengatasi kerumitan dalam komunikasi ilmiah dan juga dalam menangani perkembangan teknologi informasi (Biranvand, 2015). Penerapan yang dilakukan perpustakaan SMAN 15 Bandung dalam inovasi perpustakaan digital melalui platform edoo yaitu memberikan layanan akses koleksi perpustakaan berupa e-book, audio, video, ataupun artikel.…”
Section: Penerapan Inovasi Layanan Perpustakaan Digital Dengan Menggu...unclassified
“…However, they have been more successful than other KM processes in developing and sharing knowledge among libraries through formal and informal meetings, holding workshops, launching workgroups and asking for the librarians' cooperation in educational programmes [10]. Despite the librarians' above-medium sense of attachment to their profession in Iran, no desirable organisational conditions are considered for them to improve their knowledge capacities [34][35][36]. Thus, the Iranian community could be a good sample in learning about the effect of essential factors, such as POP on KM.…”
Section: Introductionmentioning
confidence: 99%